Tagged (example in contemporary sculptural formation) (Journal of the College of Basic Education, 2024)
Searching for the example means the great importance of the example in our existence and life, and our past, present and future. It is our supposed guide and what fills the space of the neediness of our souls and the shortcomings of our perception. So we try to imagine, interpret and imagine, seeking to approximate a form that can embody a conceptual symbol according to our perception, as our mental information does not perceive it (the symbol). Rather, you try to know it, so you begin searching for the image that is closest to it conceptually, so this formation grows little by little, and you continue updating it, until we reach with it what satisfies our desires. It is known that each of us has an identity, or an identification card that informs others about us, our orientations, and our scientific and social levels. Economic and cultural, it represents what we are, This representation that distinguishes us, one from the other, is similar to the representation of the ideal (the ideal symbol), which represents the various intellectual and conceptual trends that emerged in the period of modernity and beyond, especially in the field of plastic arts, especially the art of sculpture, and the goal of the research is to reveal the embodiment of the ideal ( The ideal symbol) in contemporary sculpture. It included some of the works of the sculptors who founded the modern art schools, European and American, in the twentieth century. The research included four chapters, and the following are the most important findings reached by the researcher:1- The process of representing the conceptual ideal represented as a form in the contemporary sculptural achievement of contemporary sculptors is considered an innovation, stemming from a particular subjective artistic vision of contemporary sculptors, when compared to the implementation of previous sculptural achievements, for the period of the twentieth century, and as stated in most of the sample models.2- The special subjective artistic vision embodied in form in the contemporary sculptural work of contemporary sculptors became clear, through non-compliance with the controls used in the implementation of previously sculptural artistic achievements in terms of standard proportions, color patterns, or surface texture, as stated in most of the sample models.3- Representations of the conceptual ideal embodied in the form of contemporary sculptural work were manifested in new images carrying a new intellectual identity that clarifies and indicates the concepts of artistic schools, as stated in most of the sample models.Contemporary artistic schools have adopted the style of abstraction, reduction, simplification and boldness in behavior, to express their identity, which represents the conceptual ideal embodied as a form in the contemporary sculptural work, as stated in many of the sample models.5- The process of representing the conceptual ideal embodied as a form in the contemporary sculptural work was clearly described through the use of unconventional materials, as stated in a number of sample models.